SERPINB3 Delays Glomerulonephritis and Attenuates the Lupus-Like Disease in Lupus Murine Models by Inducing a More Tolerogenic Immune Phenotype - Gatto, Mariele; Luisetto, Roberto; Ghirardello, Anna; Cavicchioli, Laura; Codolo, Gaia; Biasiolo, Alessandra; Maggioni, Giuseppe; Saccon, Francesca; Beggio, Marianna; Cappon, Andrea; Venturini, Roberta; Pontisso, Patrizia; et al. (Frontiers in Immunology, 2018)
Objective. To explore the effects of SERPINB3 administration in murine lupus models with a focus on lupus-like nephritis. Methods. 40 NZB/W F1 mice were subdivided into 4 groups and intraperitoneally injected with recombinant SERPINB3 (7.5μg/0.1mL or 15μg/0.1mL) or PBS (0.1 mL) before (group 1 and 2) or after (group 3 and 4) the development of proteinuria (≥100 mg/dl). Two additional mice groups were provided by including 20 MRL/lpr mice which were prophylactically injected with SERPINB3 (10 mice, group 5) or PBS (10 mice, group 6). Time of occurrence and levels of anti-dsDNA and anti-C1q antibodies, proteinuria and serum creatinine, overall- and proteinuria-free survival were assessed in mice followed up to natural death. Histological analysis was performed in kidneys of both lupus models. The Th17:Treg cell ratio was assessed by flow-cytometry in splenocytes of treated and untreated MRL/lpr mice. Statistical analysis was performed using non parametric tests and Kaplan-Meier curves, when indicated. Results. Autoantibody levels and proteinuria were significantly decreased and time of occurrence significantly delayed in SERPINB3-treated mice versus controls. In agreement with these findings, proteinuria-free and overall survival were significantly improved in SERPINB3-treated groups vs. controls. Histological analysis demonstrated a lower prevalence of severe tubular lesions in kidneys of group 5 vs. group 6. SERPINB3-treated mice showed an overall trend toward a reduced prevalence of severe lesions in both strains. Th17:Treg ratio was significantly decreased in splenocytes of MRL/lpr mice treated with SERPINB3, compared to untreated control mice. Conclusions. SERPINB3 significantly improves disease course and delays the onset of severe glomerulonephritis in lupus-prone mice, possibly inducing a more tolerogenic immune phenotype.